BRCA2 c.8827C>T pathogenic mutation in a consanguineous Chinese family with hereditary breast cancer. Issue 9 (20th July 2020) - Wang, Jiangfen; Qin, Jiayue; Xi, Chunfang; Zhang, Yafen
Abstract: Background: Mutations in the BRCA2 DNA repair associated gene ( BRCA2 ) are associated with the development of breast cancer, with different ethnic mutations at different sites. Based on different types of BRCA2 variants, the underlying mechanism remains still elusive. Methods: Next‐generation sequencing (NGS) was performed to detect germ line mutations in BRCA2 . The expressions of BRCA2 mRNA and BRCA2 protein were detected by Real‐time PCR and Western blot, respectively. Results: In a consanguineous Chinese family with hereditary breast cancer, one woman had unilateral breast cancer, two women had bilateral asynchronous breast cancer, and one man had prostate cancer. We identified a mutation site (NM_000059.4: c.8827C>T, NP_ 000050.3: p.(Gln2943*)) in BRCA2 gene, which was a nonsense mutation that predicted disrupting peptide chain synthesis and limiting BRCA2 protein production, validated by the decreased expressions of both BRCA2 mRNA and BRCA2 protein. Conclusion: In this study, we identified a BRCA2 c.8827C>T nonsense mutation with a truncated BRCA2 protein in a consanguineous Chinese Han family, suggesting individuals with this mutation should be regularly screened for malignancies such as breast, prostate, and ovarian cancer. Our study verified the function of this BRCA2 mutation site and provided a new target for the precise treatment of such patients. Abstract : We identified a BRCA2 c.8827C>T nonsense mutation with a truncated BRCA2 protein in a consanguineous Chinese Han family through next‐generation sequencing platform, suggesting individuals with this mutation should be regularly screened for malignancies such as breast, prostate, and ovarian cancer. Our study verified the function of this BRCA2 mutation site with Real‐time PCR and Western blot analysis and provided a new target for the precise treatment of such patients.